Solid-state nuclear magnetic resonance spectroscopy of cements - Walkley, B.; Provis, J.L. (Materials today advances, 2019)
Cement is the ubiquitous material upon which modern civilisation is built, providing long-term strength, impermeability and durability for housing and infrastructure. The fundamental chemical interactions which control the structure and performance of cements have been the subject of intense research for decades, but the complex, crystallographically disordered nature of the key phases which form in hardened cements has raised difficulty in obtaining detailed information about local structure, reaction mechanisms and kinetics. Solid-state nuclear magnetic resonance (SS NMR) spectroscopy can resolve key atomic structural details within these materials and has emerged as a crucial tool in characterising cement structure and properties. This review provides a comprehensive overview of the application of multinuclear SS NMR spectroscopy to understand composition–structure–property relationships in cements. This includes anhydrous and hydrated phases in Portland cement, calcium aluminate cements, calcium sulfoaluminate cements, magnesia-based cements, alkali-activated and geopolymer cements and synthetic model systems. Advanced and multidimensional experiments probe 1H, 13C, 17O, 19F, 23Na, 25Mg, 27Al, 29Si, 31P, 33S, 35Cl, 39K and 43Ca nuclei, to study atomic structure, phase evolution, nanostructural development, reaction mechanisms and kinetics. Thus, the mechanisms controlling the physical properties of cements can now be resolved and understood at an unprecedented and essential level of detail. Keywords: Solid-state NMR spectroscopy, Portland cement, Calcium aluminate cements, Calcium sulfoaluminate cements, Magnesia-based cements, Alkali-activated cements